“Boil before consumption”. Lessons to learn from the risk (mis)management case of raw milk in Italy - Finardi, Corrado; Pongolini, Stefano (Progress in Nutrition, 2014)
In 2008, a media crisis flared up and the issue triggered a prolonged “food scare”: raw milk was blamed as the cause of several cases of Haemolytic Uraemic Syndrome (HUS) due to shiga-toxin producing strains Escherichia coli, which are highly pathogenic and sometimes lethal in children. The immediate response of the Minister of Health was an urgent decree, that ordered to report “raw milk: to be boiled before consumption” in front of the distributors in red-characters and with a defined size. Therefore, instead of reassuring consumers, this warning appeared as the admission that milk was unsafe, and a confirmation that there was a real food safety problem out there. Scope of the present article is to highlight how the risk-management cycle developed, departing from the media framing of the issue. The lack of time (5 days passed from problem recognition to risk management measures) resulted in an over-conservative yet effective policy option, but at the expense of farmers, blamed of selling dangerous milk. Results suggests that there was an inverted policy-making cycle, in the try to reassure the citizens while providing a protective risk management (and at the same time allowing raw milk sales to continue, even if under rigid conditions). We consider how the framework given by the media conditioned strongly the policy measures undertaken, limiting a wider set of policy options and suggestions.